2008
DOI: 10.1083/jcb.200801099
|View full text |Cite
|
Sign up to set email alerts
|

Akt inhibition promotes autophagy and sensitizes PTEN-null tumors to lysosomotropic agents

Abstract: Although Akt is known as a survival kinase, inhibitors of the phosphatidylinositol 3-kinase (PI3K)–Akt pathway do not always induce substantial apoptosis. We show that silencing Akt1 alone, or any combination of Akt isoforms, can suppress the growth of tumors established from phosphatase and tensin homologue–null human cancer cells. Although these findings indicate that Akt is essential for tumor maintenance, most tumors eventually rebound. Akt knockdown or inactivation with small molecule inhibitors did not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
297
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(331 citation statements)
references
References 76 publications
30
297
1
3
Order By: Relevance
“…6C), which may account for the rapid phenotypic changes associated with apoptosis and autophagy seen in Fig. 1B and C. Akt is cleaved during apoptosis, resulting in its inactivation and subsequent induction of autophagy (31,32). Levels of active Ser473 phosphorylated Akt increased until 8 hours, when Akt cleavage peaked, then declined to baseline levels.…”
Section: Combined Selinexor/carfilzomib Treatment Overcomes Cytoprotementioning
confidence: 86%
See 1 more Smart Citation
“…6C), which may account for the rapid phenotypic changes associated with apoptosis and autophagy seen in Fig. 1B and C. Akt is cleaved during apoptosis, resulting in its inactivation and subsequent induction of autophagy (31,32). Levels of active Ser473 phosphorylated Akt increased until 8 hours, when Akt cleavage peaked, then declined to baseline levels.…”
Section: Combined Selinexor/carfilzomib Treatment Overcomes Cytoprotementioning
confidence: 86%
“…We also assessed levels of total Akt and its activation state given its pivotal role in myeloma cell survival and drug resistance (30), and its ability to limit autophagy (31). Interestingly, we found simultaneous activation of caspase-10, -8, -9, and -3 and cleavage of both PARP and Akt beginning 6 hours after treatment (Fig.…”
Section: Combined Selinexor/carfilzomib Treatment Overcomes Cytoprotementioning
confidence: 95%
“…For instance, it could act as a switch that controls a major cellular energy consumer, mTORC1, and a major energy producer, Akt. But also could have an important role to inhibit autophagy [47][48][49][50] which is an important process to prevent autophagy-mediated cell death. 47,51 Cytokine-driven autophagy has been observed in several pathological conditions including atherosclerosis, 52 myopathy 53 and arthritis, 54 which has been linked to TNFα and IFNγ presence.…”
Section: Discussionmentioning
confidence: 99%
“…But also could have an important role to inhibit autophagy [47][48][49][50] which is an important process to prevent autophagy-mediated cell death. 47,51 Cytokine-driven autophagy has been observed in several pathological conditions including atherosclerosis, 52 myopathy 53 and arthritis, 54 which has been linked to TNFα and IFNγ presence. But, contrary to those reports where autophagy acts as a suicidal mechanism, 55,56 our results suggested that the major purpose of the accompanying increase in autophagy observed during inflammation is to fully activate Akt1, a major antiapoptotic signaling molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the membrane, PDK1 and mammalian target of rapamycin 1 (mTOR1) activate Akt through phosphorylation at various sites. Thus, the activated Akt positively regulated cell growth or activity, but negatively regulated cell autophagy and apoptosis (13). PTEN has been demonstrated to be the essential molecule regulating PI3K/AKT pathways and consequently various cell destinations (14).…”
Section: Introductionmentioning
confidence: 99%